Infrared Thermographic Assessment of Spinal Anesthesia-related Temperature Changes During Cesarean Section. Issue 4 (21st December 2022) - Murphy, B.; McCaul, C.C.L.; O'Flaherty, D.
Abstract : ( Int J Obstet Anes . 2022;49:103245) Spinal anesthesia is often assessed by the subjective method of cold and light touch perception. Inadequate anesthesia can cause pain during surgery and negligence claims. Infrared thermography (ITH) objectively measures skin surface temperature, which increases during spinal anesthesia due to blood vessel dilatation and increased blood flow. There have been conflicting results in studies investigating skin temperature changes during neuraxial anesthesia in nonpregnant patients. This study aimed to determine whether ITH measured consistent and significant skin temperature changes during spinal anesthesia for cesarean delivery (CD).